THE EFFECT OF ORGANIZATIONAL COMMITMENT AND WORK MOTIVATION ON TURNOVER INTENTION AT CV PIRAMIDA JAYA - Lawati, Susi (Journal of Business and Management Inaba, 2023)
This research focuses on the turnover rate of CV Piramida Jaya Bandung which varies from 2019 to 2022. However, this research also intends to understand organizational commitment, work motivation, turnover intention, and the extent to which organizational commitment and work motivation influence simultaneously and partially. employee turnover at CV Pyramid Jaya. This study uses a quantitative research design with descriptive and verification methodologies, with data collection through questionnaires, interviews, observations, and literature studies. The study population was all employees of CV Piramida Jaya, totaling 60 people, with a saturation sample which incidentally could represent all employees. Organizational commitment (X1) and work motivation (X2) are independent variables, and turnover intention (Y) is the dependent variable. Validity, reliability, and traditional assumption tests are part of data analysis. Data processing using statistical product and service solution software includes data analysis methods linear regression analysis, correlation, determination, T test, and F. Thus it is hoped that this research can explain the variables that influence CV Piramida Jaya employees' intentions to leave their jobs and offers useful advice for human resource management. According to the results of the questionnaires filled out by respondents, the main cause of employee intention to leave the company is a lack of commitment which is revealed through poor training and lack of employee attendance because it does not support careers and employees. development. Regression analysis and other appropriate statistical methods will be used to analyze the data to determine the impact of organizational commitment and work motivation on turnover intention. Also anticipated from the study findings are ideas or recommendations to improve CV Piramida Jaya's human resource management and better knowledge about the factors that affect the turnover rate in the company.